Pelatihan Gaya Hidup Sehat dan Pencegahan Perilaku Merokok di Kalangan Remaja - ratna damayanti; Alifiani; Anies Fuady (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2025)
The initial knowledge of SMPN 1 Bantaran students about the dangers of smoking and addictive substances is still low (average 27.39/43) with misconceptions in 19-38% of students, indicating the urgency of school-based educational interventions. This community service program aims to improve understanding and skills in smoking prevention through interactive, data-driven training. Participatory methods included needs analysis, interactive lectures, role-plays, quizzes, and pre-post-test evaluations on 161 students. Results showed a significant increase in knowledge, with an average correct post-test score of 85-90%. In conclusion, the interactive approach is effective in increasing retention and positive attitudes toward a healthy lifestyle. Consequently, this program recommends integrating prevention materials into the curriculum, establishing anti-smoking ambassadors, and involving parents to ensure the sustainability of prevention efforts among adolescents.